2015
DOI: 10.1016/j.ejpb.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Rapid conversion of the ester prodrug abiraterone acetate results in intestinal supersaturation and enhanced absorption of abiraterone: In vitro, rat in situ and human in vivo studies

Abstract: The aim of this study was to evaluate the intestinal disposition of abiraterone acetate, an ester prodrug of the anticancer agent abiraterone. Stability of the prodrug and solubility and dissolution characteristics of both abiraterone and abiraterone acetate were monitored in vitro. Moreover, the in vivo intraluminal concentrations of abiraterone and abiraterone acetate upon intake of one tablet of 250 mg abiraterone acetate were assessed in healthy volunteers. The intestinal absorption resulting from the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 11 publications
1
51
1
Order By: Relevance
“…Enabling formulations such as solid dispersions, nano-and microparticles and cyclodextrin/co-solvent based solutions are examples of methods used to increase solubilization or achieve supersaturated solution of the drug, with the ultimate goal of enhancing oral absorption. Aspiration of gastric and duodenal fluids in parallel with blood sampling resulted in new insights into how these enabling strategies behave after oral intake (Brouwers et al, 2006;Hens et al, 2015a;Stappaerts et al, 2015). Moreover, drug solubility measurements in these aspirated fluids can reveal whether the drug was supersaturated at the time of aspiration or directly started to precipitate (Hens et al, 2015b;Psachoulias et al, 2011;Van Den Abeele et al, 2015).…”
Section: Invasive Methodologiesmentioning
confidence: 99%
“…Enabling formulations such as solid dispersions, nano-and microparticles and cyclodextrin/co-solvent based solutions are examples of methods used to increase solubilization or achieve supersaturated solution of the drug, with the ultimate goal of enhancing oral absorption. Aspiration of gastric and duodenal fluids in parallel with blood sampling resulted in new insights into how these enabling strategies behave after oral intake (Brouwers et al, 2006;Hens et al, 2015a;Stappaerts et al, 2015). Moreover, drug solubility measurements in these aspirated fluids can reveal whether the drug was supersaturated at the time of aspiration or directly started to precipitate (Hens et al, 2015b;Psachoulias et al, 2011;Van Den Abeele et al, 2015).…”
Section: Invasive Methodologiesmentioning
confidence: 99%
“…(Jarkko et al, 2008) It has been demonstrated, however, that premature intraluminal hydrolysis mediated by hydrolyzing enzymes present in the intestinal fluids may significantly alter the intestinal absorption of a prodrug. (Brouwers et al, 2007); (Stappaerts et al, 2015) It has for instance been shown that intraluminal degradation of the ester prodrug tenofovir disoproxil fumarate takes place in vivo, illustrating that the esterases present in the intestinal fluids may undermine the intended enhanced permeability. In another recently described study, the hydrolyzing capacity of intestinal fluids was revealed to be an effective trigger causing abiraterone supersaturation upon administration of the ester prodrug abiraterone acetate; esterase-mediated hydrolysis was shown to be beneficial for the intestinal absorption of abiraterone.…”
Section: Introductionmentioning
confidence: 98%
“…In another recently described study, the hydrolyzing capacity of intestinal fluids was revealed to be an effective trigger causing abiraterone supersaturation upon administration of the ester prodrug abiraterone acetate; esterase-mediated hydrolysis was shown to be beneficial for the intestinal absorption of abiraterone. (Stappaerts et al, 2015) It is clear that the intraluminal behavior of ester prodrugs can be diverse and may have significant repercussions on intestinal drug absorption. In vitro stability testing in biorelevant media containing hydrolyzing enzymes is clearly an important step in assessing the feasibility of a prodrug approach.…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence in the literature that lipolysis of a self-846 microemulsifying drug delivery system may lead to the formation of 847 an amorphous precipitate [81]. Both prodrug conversion [82] and 848 dissolution of cocrystals [83] can generate supersaturated solutions, 849 hence these are unexplored potential routes that could result in LLPS.…”
mentioning
confidence: 98%